Differentiating Nonrestorative Sleep from Nocturnal Insomnia Symptoms: Demographic, Clinical, Inflammatory, and Functional Correlates - Zhang, Jihui (Associated Professional Sleep Societies, LLC, 2013)
STUDY OBJECTIVES: Recent studies have suggested that nonrestorative sleep (NRS) symptoms may be distinct from nocturnal insomnia symptoms (NIS). However, there is limited information on the demographic, medical, and biologic correlates of NRS independent from NIS in the general population. This report presents the sociodemographic correlates, patterns of comorbidity with other sleep and physical disorders, C-reactive protein (CRP) levels, and general productivity associated with NIS and NRS in a nationally representative sample of US adults. DESIGN: National Health and Nutrition Examination Survey (NHANES). SETTING: The 2005-2008 surveys of the general population in the United States. PARTICIPANTS: There were 10,908 individuals (20 years or older) INTERVENTIONS: N/A. MEASUREMENTS AND RESULTS: Respondents were classified by the presence or absence of NIS and NRS. Compared with those without insomnia symptoms, respondents with NIS were older and had lower family income and educational levels than those with NRS. In addition, there was a significant association between NIS and cardiovascular disease, whereas NRS was associated with other primary sleep disorders (including habitual snoring, sleep apnea, and restless legs syndrome), respiratory diseases (emphysema and chronic bronchitis), thyroid disease, and cancer as well as increased CRP levels. In addition, the study participants with NRS only reported poorer scores on the Functional Outcomes of Sleep Questionnaire (FOSQ) than those without insomnia symptoms or those with NIS only. CONCLUSIONS: These findings suggest that there are substantial differences between NIS and NRS in terms of sociodemographic factors, comorbidity with other sleep and physical disorders, increased CRP level, and functional impairment. An inflammatory response might play a unique role in the pathogenesis of NRS. CITATION: Zhang J; Lamers F; Hickie IB; He JP; Feig E; Merikangas KR. Differentiating nonrestorative sleep from nocturnal insomnia symptoms: demographic, clinical, inflammatory, and functional correlates. SLEEP 2013;36(5):671-679.